Legal Status and Inheritance Rights for Adapted Children That Are Not Applyed by a Court Decision - Ida Ayu Kade Irsyanti Nadya Saraswati (Journal Equity of Law and Governance, 2022)
The purpose of a marriage is to form a family and continue offspring. But not all families are lucky to have a child. One way to overcome this is by adopting a child. Adoption of a child can be carried out based on national law or customary law. Adoption of children based on customs in Government Regulation No. 54 of 2007 is not required to obtain a court decision. This will cause problems related to inheritance rights for adopted children who are not requested for a court decision. On the one hand, this provides legal certainty for customary law because it is recognized by national law, but on the other hand, without written evidence, if there is a dispute over inheritance rights in court, the position of the adopted child is not strong enough if he does not have written evidence.